2016
DOI: 10.18632/oncotarget.11637
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of lncRNA-mRNA related ceRNA network across 12 major cancers

Abstract: Recent studies indicate that long noncoding RNAs (lncRNAs) can act as competing endogenous RNAs (ceRNAs) to indirectly regulate mRNAs through shared microRNAs, which represents a novel layer of RNA crosstalk and plays critical roles in the development of tumor. However, the global regulation landscape and characterization of these lncRNA related ceRNA crosstalk in cancers is still largely unknown. Here, we systematically characterized the lncRNA related ceRNA interactions across 12 major cancers and the normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(113 citation statements)
references
References 65 publications
(91 reference statements)
4
109
0
Order By: Relevance
“…Mounting evidence has demonstrated that lncRNAs are closely associated with normal physiological progresses and pathological change [26]. The aberrantly expressed lncRNAs could be applied as prediction biomarkers for many diseases, including cancers [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has demonstrated that lncRNAs are closely associated with normal physiological progresses and pathological change [26]. The aberrantly expressed lncRNAs could be applied as prediction biomarkers for many diseases, including cancers [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of researches have demonstrated the dysregulated expressions of lncRNAs in varieties of cancers, including breast cancer, cervical cancer, prostate cancer, oesophageal squamous cell carcinoma, colorectal cancer, nasopharyngeal carcinoma, hepatocellular carcinoma, osteosarcoma and gastric cancer [13]. One of the commonest dysregulation forms of lncRNA is elucidated by Iyer et al's [14]integrative analyses of approximately 7200 RNA-sequencing libraries from cancer and non-cancer tissues and cells, which identified over 8000 cancerrelated lncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Hub nodes, which have been examined in some studies and are characterized by their high degree of connectivity to other nodes in the ceRNA network, can be used as topological properties of the ceRNA network to assess the significance of genes [39,40]. In the present study, four lncRNAs (DNAJC27-AS1, AF121898, OIP5-AS1, and SNX29P2) were observed to be topological hub nodes whose betweenness, network degree, and closeness centrality were significantly higher in comparison with other lncRNAs.…”
Section: Discussionmentioning
confidence: 99%